Thermodynamic Model of a Very High Efficiency Power Plant based on a Biomass Gasifier, SOFCs, and a Gas Turbine - P V Aravind; C Schilt; B Türker; T Woudstra (International Journal of Renewable Energy Development, 2012)
Thermodynamic calculations with a power plant based on a biomass gasifier, SOFCs and a gas turbine are presented. The SOFC anode off-gas which mainly consists of steam and carbon dioxides used as a gasifying agent leading to an allothermal gasification process for which heat is required. Implementation of heat pipes between the SOFC and the gasifier using two SOFC stacks and intercooling the fuel and the cathode streams in between them has shown to be a solution on one hand to drive the allothermal gasification process and on the other hand to cool down the SOFC. It is seen that this helps to reduce the exergy losses in the system significantly. With such a system, electrical efficiency around 73% is shown as achievable.